The Role of Virtual Consulting in Developing Environmentally Sustainable Health Care: Systematic Literature Review - Martha Pickard Strange; Amy Booth; Melissa Akiki; Sietse Wieringa; Sara E Shaw (JMIR Publications, 2023)
BackgroundHealth systems globally need to rapidly set and achieve targets for reaching net zero carbon emissions. Virtual consulting (including video- and telephone-based consulting) is regarded as one means by which this might be achieved, largely through reduced patient travel. Little is currently known about the ways in which forms of virtual consulting might contribute to the net zero agenda or how countries may develop and implement programs at scale that can support increased environmental sustainability. ObjectiveIn this paper, we asked, What is the impact of virtual consulting on environmental sustainability in health care? and What can we learn from current evaluations that can inform future reductions in carbon emissions? MethodsWe conducted a systematic review of published literature according to PRISMA (Preferred Reporting Item for Systematic Reviews and Meta-Analyses) guidelines. We searched the MEDLINE, PubMed, and Scopus databases using key terms relating to "carbon footprint," "environmental impact," "telemedicine," and "remote consulting," using citation tracking to identify additional articles. The articles were screened, and full texts that met the inclusion criteria were obtained. Data on the approach to carbon footprinting reported reductions in emissions, and the opportunities and challenges associated with the environmental sustainability of virtual consultations were extracted into a spreadsheet, analyzed thematically, and theorized using the Planning and Evaluating Remote Consultation Services framework to consider the various interacting influences, including environmental sustainability, that shape the adoption of virtual consulting services. ResultsA total of 1672 papers were identified. After removing duplicates and screening for eligibility, 23 papers that focused on a range of virtual consulting equipment and platforms across different clinical conditions and services were included. The focus on the environmental sustainability potential of virtual consulting was unanimously reported through carbon savings achieved by a reduction in travel related to face-to-face appointments. The shortlisted papers used a range of methods and assumptions to determine carbon savings, reporting these using different units and across varied sample sizes. This limited the potential for comparison. Despite methodological inconsistencies, all papers concluded that virtual consulting significantly reduced carbon emissions. However, there was limited consideration of wider factors (eg, patient suitability, clinical indication, and organizational infrastructure) influencing the adoption, use, and spread of virtual consultations and the carbon footprint of the entire clinical pathway in which the virtual consultation was provided (eg, risk of missed diagnoses from virtual consultations that result in the need for subsequent in-person consultations or admissions). ConclusionsThere is overwhelming evidence that virtual consulting can reduce health care carbon emissions, largely through reducing travel related to in-person appointments. However, the current evidence fails to look at system factors associated with implementing virtual health care delivery and wider research into carbon emissions across the entire clinical pathway.